STUDY OF THE EXISTING SYSTEM OF LOGISTICS SUPPORT IN CONSTRUCTION - V. Opekunov; T. Martirosyan (Вестник университета)
The article deals with the concept of logistics, presents particular logistical support in a number of countries. The role and significance of the subsystem of logistics in the construction industry. The problems of logistics in the field of construction. The article suggests measures to improve the system of logistics domestic construction industry.